Manual for Sustainable Management of Clumping Bamboo Forest - Durai, J.; Trinh, T.L. (2020)
Bamboo is a plant that belongs to the true grass family Poaceae, a subfamily of Bambusoideae. Bamboo is one of the fastest growing plants in the world. There are over 1600 bamboo species naturally distributed in tropical and subtropical belts, and they are commonly found in Africa, Asia and Central and South America. Some species can also successfully grow in the temperate regions of Europe and North America. Bamboo has a unique, dense rhizome structure that helps in accelerating the growth rate of bamboo shoots and culms annually. Thanks to special biological characteristics of the rhizome, when a bamboo culm is harvested, the bamboo rhizome system is still alive and continues to produce shoots. Bamboo matures in 3–5 years, and thereafter, it can be harvested annually for about 20 years or longer, depending on the gregarious flowering period, after which bamboo dies. Bamboo’s gregarious flowering interval can be between 20 and 120 years depending on the species and location. There are two main types of bamboo rhizome, which are as follows: (a) monopodial (running) and (b) sympodial (clumping). Running bamboo has a rhizome that spreads horizontally and forms dispersed bamboo culms, whereas clumping bamboo has a shorter rhizome, is formed together and generates bamboo clumps. Running bamboo can spread quickly, while clumping bamboo stays together in its cluster. This means that harvesting clumping bamboo is more difficult than harvesting running bamboo is, especially because in clumping bamboo, most of the mature culms are located in the centre of the clump. Bamboo is a perennial plant that easily adapts to different site conditions. It can grow in a wide variety of soil types, ranging from organic-poor to mineral-rich and from drought to flooding conditions where many plants cannot grow. Bamboo can grow rapidly in hot and humid rainforests and even in cold climates with temperatures around −0°C. It has an extensive rhizome and root system that makes it capable of stabilising loose soil to prevent soil erosion. Bamboo is a versatile multipurpose plant, with over 10,000 products and applications ranging from timber substitute, construction materials, food and beverages, bio-energy, pulp and paper, fibre composites, textiles, lifestyle products and traditional sustenance use products. With recent technological innovations, a wide range of high end industrial products have been produced and traded globally. Annual bamboo trade was estimated at a value of USD 60 billion in 2017, half of which was conducted in China. Many countries realised the socio-economic and environmental benefits of bamboo; however, due to a lack of knowledge for establishment and management of bamboo, especially for clumping bamboo, the potential of bamboo is still untapped in many countries. This manual aims to support people who work in the field for the establishment and management of bamboo plantation. The manual has been developed based on the International Bamboo and Rattan Organisation’s projects, especially the Dutch-Sino East Africa Bamboo Development Programme in Ethiopia, Kenya and Uganda and South–outh Knowledge Transfer Strategies for Pro-Poor Bamboo Livelihoods in Ethiopia, Madagascar and Uganda. The manual guides step-by-step for production of bamboo seedlings and planting, maintaining and sustainably harvesting bamboo plantations. This manual comprises five chapters. Chapter one provides an explanation of terms in the manual, and chapter two offers step-bystep instructions for propagating bamboo through culm cutting, branch cutting, air layering, macro-proliferation, rhizomes and seeds. Chapter three provides guidelines for the establishment of bamboo plantations. Chapter four explains how to maintain bamboo plantations and inter-crop other crops in bamboo plantations. Chapter five provides instructions for sustainable management of bamboo plantations.